2015
DOI: 10.1002/adma.201501708
|View full text |Cite
|
Sign up to set email alerts
|

Multistable Architected Materials for Trapping Elastic Strain Energy

Abstract: 3D printing and numerical analysis are combined to design a new class of architected materials that contain bistable beam elements and exhibit controlled trapping of elastic energy. The proposed energy-absorbing structures are reusable. Moreover, the mechanism of energy absorption stems solely from the structural geometry of the printed beam elements, and is therefore both material- and loading-rate independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
459
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 738 publications
(466 citation statements)
references
References 24 publications
4
459
1
2
Order By: Relevance
“…Examples range from the macroscale-where 3D-printed stacks of bistable beams absorb impact energy [237,238]-down to the nanoscale-where carbon nanotube buckling was explored to serve the same purpose [239]. In a similar spirit, multistable magnetoelastic structures (where multistability arises from the combination of magnetic and elastic interactions) were shown to efficiently absorb impact energy [240].…”
Section: Multistability and Nonlinear Metamaterialsmentioning
confidence: 99%
“…Examples range from the macroscale-where 3D-printed stacks of bistable beams absorb impact energy [237,238]-down to the nanoscale-where carbon nanotube buckling was explored to serve the same purpose [239]. In a similar spirit, multistable magnetoelastic structures (where multistability arises from the combination of magnetic and elastic interactions) were shown to efficiently absorb impact energy [240].…”
Section: Multistability and Nonlinear Metamaterialsmentioning
confidence: 99%
“…Shan et al [215] demonstrated the accessibility of fabricating bistable structures by 3D printing multi-stable, architected materials. When compressed, the internal beam elements move into another stable state but with higher energy, exhibiting local, bistable deformation.…”
Section: Multi-stable Structuresmentioning
confidence: 99%
“…soft | mechanical signal | stable propagation | instability S oft, highly deformable materials have enabled the design of new classes of tunable and responsive systems and devices, including bioinspired soft robots (1, 2), self-regulating microfluidics (3), adaptive optics (4), reusable energy-absorbing systems (5,6), structures with highly programmable responses (7), and morphological computing paradigms (8). However, their highly deformable and dissipative nature also poses unique challenges.…”
mentioning
confidence: 99%